Autumn Falls : a novel - Thorne, Bella, 1997-; Allen, Elise (Thorne, Bella, 1997- Autumn Falls novel., 2014)
"Following her adored father's death, a teenager named Autumn Falls is forced to relocate to a new school in Florida for sophomore year. And when Autumn receives an enchanted gift: a journal that literally brings Autumn's writing to life--anything could happen. Could the journal be imbued with her dad's spirit?"--